MTJ-based asynchronous circuits for Re-initialization free computing against power failures. (December 2018) - Onizawa, N.; Imai, M.; Yoneda, T.; Hanyu, T.
Abstract: This paper introduces CMOS/magnetic tunnel junction (MTJ)-based asynchronous circuits for re-initialization free computing against power failures. The use of MTJ devices can realize continuous operations upon frequent power failures as data being processed are stored with nonvolatility. As asynchronous circuits exploit local control signals instead of a global clock signal, the MTJ-based asynchronous circuits can immediately restart operations after the power supply is recovered without waiting for the calibration time of phase-locked loops used in synchronous circuits. For the safe restore operations, the proposed circuits address issues of metastable states that might occur in the backup phase because of different timings of local control signals. In addition, write-reliable nonvolatile keepers (latches) are introduced in order to reduce write-error rates of MTJ devices for the safe backup operations. To evaluate the performance overheads due to the nonvolatile operations, the proposed asynchronous circuits are designed using TSMC 65 nm CMOS technology and a three-terminal MTJ model and are compared with conventional volatile asynchronous circuits in several benchmarks.